2023
DOI: 10.1177/23998083221147922
|View full text |Cite
|
Sign up to set email alerts
|

A barrier too far: Understanding the role of intersection crossing distance on bicycle rider behavior in Chicago

Abstract: For a variety of environmental, health, and social reasons, there is a pressing need to reduce the automobile dependence of American cities. Bicycles are well suited to help achieve this goal. However, perceptions of rider safety present a large hindrance toward increased bicycle adoption. These perceptions are largely influenced by the design of our current road infrastructure, including the crossing distances of large intersections. In this paper, we examine the role of intersection crossing distances in mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…In addition to safety and connectivity related questions, it is important to understand how citizens use the cycling networks based on their preferences, in order to better design and plan for cycling infrastructure. Aras et al (2023) investigated the role of intersection crossings as physical barriers to cycling based on bikeshare data from Chicago, USA. They found that bikeshare riders prefer avoiding large intersections in circumstances when it is possible to do so.…”
Section: Developing Cycling Infrastructure With Data-driven Approachesmentioning
confidence: 99%
“…In addition to safety and connectivity related questions, it is important to understand how citizens use the cycling networks based on their preferences, in order to better design and plan for cycling infrastructure. Aras et al (2023) investigated the role of intersection crossings as physical barriers to cycling based on bikeshare data from Chicago, USA. They found that bikeshare riders prefer avoiding large intersections in circumstances when it is possible to do so.…”
Section: Developing Cycling Infrastructure With Data-driven Approachesmentioning
confidence: 99%